Structural, magnetic, impedance and electric modulus response and dielectric relaxation in Co-doped inverse spinel CuFe2O4 nanoferrite - Sudhir Minz; S.C. Sahoo; S.K. Rout; Manoranjan Kar; Banarji Behera (Chemical Physics Impact, 2024)
In this research work, we report synthesis, structural, electric and magnetic properties of Cu1−XCoXFe2O4(x = 0.05, 0.10, 0.15, 0.20) nanoferrite. All the samples are synthesized using sol-gel auto-combustion method. X-ray diffraction patterns validate the formation of single phase tetragonal structure at room temperature for all the samples. Absence of secondary phases confirms the successful substitution of Cu2+ by Co2+ ions in CuFe2O4 matrix. Dielectric analysis reveals that all the materials exhibit remarkable single dielectric relaxation. The dielectric relaxation peaks are observed between 150–225 °C. In addition, Co-doped CuFe2O4 exhibit marked enhancement of dielectric constant value for potential technological applications. Further, the correlated barrier hopping (CBH) model well explains the conduction phenomena in all the samples. Activation energy values are analyzed by applying the Arrhenius equation. Impedance analysis indicates that both grain and grain boundary effects contributed the electrical response in the ferrites which is confirmed from the plot of Z″ vs. Z′. The bulk and grain boundary response are further determined by modeling the impedance data with an equivalent circuit. Modulus study confirms the existence of non-Debye type of relaxation in the synthesized ferrites. Magnetic study shows the improved value of magnetic parameters such as saturation magnetization (Ms), remanent magnetization (Mr) and coercive field (Hc).